THE USE OF PAIRED READING STRATEGY IN TEACHING READING SKILLS TO EFL STUDENTS (A case study of the 8th grade of Junior High School in Antapani) - Arief Fajar Gumilar, - (2018)
This study focused on the investigation of the use of paired reading strategy in teaching reading to the EFL students in one junior high schools in Bandung and how the students reacted to the implementation of paired reading strategy in EFL classroom. The mix method case study was employed to obtain the data. This study involved eighth grade students as the research participants. The data were collected from classroom observation, questionnaire, post activity quiz, and interview. The data collected were analyzed using scoring rubric adapted from Topping (2001). This study revealed that the use of paired reading strategy in the form of paired reading activities in the EFL classroom provides several beneficial uses toward the EFL students. First, the activity helped the students to understand the text thus improving their reading skills in general. Second, the paired reading activities helped the students in improving their vocabulary knowledge. Third, the activities increased students' reading rates and fluency. Fourth, paired reading strategy encouraged the students to share the information they acquired from the text. Last but not least, the activities helped to motivate and develop students' interest in reading English text. ---Penelitian ini bertujuan untuk menyelidiki kegunaan strategi paired reading dalam pembelajaran reading kepada siswa EFL (English as foreign language) di salah satu sekolah menengah pertama (SMP) di Bandung serta mencari tahu respon para siswa terhadap implementasi dari strategi tersebut di dalam kelas Bahasa Inggris. Metode penelitian campuran dalam bentuk studi kasus digunakan dalam penelitian ini untuk memperoleh data. Studi ini melibatkan siswa-siswa kelas delapan sebagai partisipan. Data studi diperoleh melalui observasi kelas, kuesioner, kuis pasca aktivitas, dan wawancara. Data-data tersebut kemudian diproses menggunakan rubrik penilaian yang diadaptasi dari Topping (2001). Penelitian ini mengungkap bahwa pelaksanaan kegiatan paired reading dalam pembelajaran Bahasa Inggris memberikan beberapa manfaat bagi siswa EFL. Pertama, aktivitas tersebut membantu siswa memahami teks yang menunjukkan peningkatan kemampuan reading mereka secara umum. Kedua, paired reading membantu siswa mengembangkan pengetahuan kosa kata Bahasa Inggris. Ketiga, strategi paired reading meningkatkan kecepatan dan kelancaran membaca siswa. Keempat, strategi ini membuat siswa lebih berani untuk berbagi informasi dari bahan baca yang diberikan. Terakhir, strategi ini membantu memotivasi siswa serta mengembangkan ketertarikan mereka untuk membaca lebih banyak teks Bahasa Inggris.